Follow Up Imaging in Hepatocellular Cancer Ultrasound Screening Exams With Poor Visualization Scores. (5th September 2022) - Bley, Edward; Mohan, Nandakumar; Jackson, Inimfon; Chaisidhivej, Natapat; Jarrett, Simone; Lo, Kevin Bryan; Navarro, Victor; Rossi, Simona; Rodgers, Shuchi K.; Kalman, Richard S.
Abstract : Objectives: The Ultrasound Liver Imaging Reporting and Data Systems (LI‐RADS) provides standardized terminology and reporting for ultrasound (US) examinations performed for hepatocellular cancer (HCC) screening. However, there are no recommendations regarding follow up imaging for visualization scores with suboptimal visualization. Therefore, the aim of this study is to examine follow up imaging practices in the setting of US studies scored as B (moderate limitations) and C (severe limitations). Methods: A single center retrospective analysis of studies from 2017 to 2021 with HCC US screening visualization scores of B and C was performed. Follow up imaging with US, CT, or MRI within 6 months with visualization score B or C on initial US were included. Results: Five hundred and sixty HCC US studies with suboptimal imaging were reviewed. Of those with follow up imaging, patients with a visualization score of B underwent US in more than half (58%) of the cases while those with visualization score of C underwent more CT/MRI studies (62.5%, P = .12) Patients with visualization score of B had more MRI exams performed (55%) while patients with a visualization score of C underwent more CT exams (70%, P = .16). Conclusions: Currently, there are no guidelines instructing follow up imaging on HCC screening ultrasounds with poor visualization, and the data suggests that providers have taken a heterogeneous approach. This suggests a need for society recommendations on how to approach HCC screening ultrasounds in patients with suboptimal studies.